1999
DOI: 10.1080/1353832990050206
|View full text |Cite
|
Sign up to set email alerts
|

Generic Descriptors: a health check

Abstract: The Credit Accumulation and Transfer Scheme (CATS) is a system that awards academic credits for achievement. Credits are awarded at different levels: 1, 2 and 3 (associated with the three full-time years of study on an undergraduate course in Britain) and level M (associated with British Master's qualifications). This paper will scrutinise two of the assumptions upon which CATS is based: (1) there are comparable notions of levels 1, 2, 3 and M across both institutions and disciplines, and (2) there is linear p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…18. Difficulties are reported in getting agreement on criteria and their application in a subject (Greatorex, 1999;Woolf et al, 1999) and in a School (Price & Rust, 1999).…”
Section: Assessment In Quality Monitoringmentioning
confidence: 99%
“…18. Difficulties are reported in getting agreement on criteria and their application in a subject (Greatorex, 1999;Woolf et al, 1999) and in a School (Price & Rust, 1999).…”
Section: Assessment In Quality Monitoringmentioning
confidence: 99%
“…A great deal of time and effort has been used to construct level descriptors and gain an agreement on their wording. Greatorex (1999) found that HE educators could agree on the appropriate levels for descriptors, but this does not indicate how the level descriptors are used, e.g., they might not be applied consistently. The uses of level descriptors, i.e., the consistent application of the level descriptors and developing an understanding of level descriptors, are discussed below.…”
Section: The Process Of Developing Level Descriptorsmentioning
confidence: 94%
“…Greatorex (1999) explains that when educators write level descriptors to cover a variety of disciplines and professions (generic descriptors)-for example, in Higher Education Credit Accumulation and Transfer Schemes-they can be so general that they are meaningless. Additionally, a study by Winter (1993) found that similar words are used to describe achievement at different levels, e.g., Masters level and undergraduate level.…”
Section: Applying Level Descriptorsmentioning
confidence: 98%
See 1 more Smart Citation
“…A growing body of literature around the experience of criterion-referenced assessment has elaborated on problematic as well as beneficial aspects (Greatorex, 1999;Price & Rust, 1999;Ecclestone, 2001;Rust, 2001;Dunn et al, 2002;Knight, 2002a, b;Hornby, 2003;Miller, 2003;Sadler, 2003Sadler, , 2005Taras, 2003;Orsmond et al, 2004;Woolf, 2004;O'Donovan et al, 2005). As suggested by titles such as 'How criteriabased grading misses the point' (Sadler, 2003) and 'Summative assessment in higher education: practices in disarray' (Knight, 2002b), policy implementation can be far from straightforward.…”
Section: Developing Generic Criteria and Standards For Assessment 419mentioning
confidence: 99%